Iowa gems and minerals in your pocket - Garvin, Paul, 1939- (Bur Oak guide., 2012)
From the spiky teeth of a geode containing sparkling quartz crystals, the rich browns and golds of smoky quartz and goethite needles on calcite, and the coral-like branches of plumose barite to the abstract reds and whites of polished agate cabochons, world-class mineral crystals are harvested from the rocks of the Hawkeye State. Collecting these high-quality crystals requires access to active mines, pits, and quarries, and individual collectors are rarely allowed entrance to these facilities. With information about each specimen's type, source, size, and current location, Paul Ga.